Pengaruh Pola Tidur terhadap Kejadian Hipertensi: Studi Kasus-Kontrol pada Nelayan di Pesisir Puger Kabupaten Jember - Astuti, Nur Fitri Widya; Munawaroh, Nazilatul Wahyuni (Jurnal Biomedika dan Kesehatan, 2024)
Background Hypertension prevalence in coastal areas is higher (53.3%) than in mountainous areas (6.8%). The high prevalence of hypertension in coastal areas is caused by lifestyle, one of which is poor sleep patterns. The research purpose was to determine the effect of sleep patterns on hypertension incidence in Puger fishermen. Methods This research used a Case-Control design. This research was conducted in February-March 2023. The research sample was calculated using a formula Lemeshow and there were 31 respondents in each group for a total of 62 respondents. The sampling technique used simple random sampling and the data taken included the variables hypertension and sleep patterns which consist of quality, duration, latency, efficiency, sleep disturbances, use of sleeping pills, and concentration problems during the day. Analysis data used frequency distribution for univariate analysis and tests Chi-Square and Fisher for bivariate analysis. Results The results showed that both groups had short sleep duration, it’s <7 or 8 hours. The results showed that 93.5% of fishermen in the case group experienced poor sleep patterns (score>5), while as many as 45.2% of fishermen in the control group experienced poor sleep patterns. Obtained (p-value <0.001; OR 17.6; CI 95%: 3.6-87.0), which means that the influence between sleep patterns and hypertension is the incidence in Puger fishermen and the OR value is 17.6 indicates that fishermen who have a poor sleep pattern have a 17.6 times risk attacked of hypertension than fishermen who have a good sleep pattern. Conclusions Sleep pattern is a risk factor for hypertension in Puger fishermen, so it’s recommended that respondents implement sleep patterns by optimizing sleeping hours as well and for The Puger Community Health Center to encourage respondents to utilize the facilities so they can monitor symptoms of hypertension.